China’s Electric Vehicle Market: Issues and Solutions - Wang Yumeng (SHS Web of Conferences)
The Chinese electric vehicle (EV) market has emerged as a global leader, with an estimated value of $305.57 billion in 2024, projected to grow to $674.27 billion by 2029. However, despite this promising outlook, the industry faces several economic and financial challenges, such as high production costs, market overcapacity, reliance on government subsidies, and consumer preferences for traditional brands. High production costs, particularly associated with battery technology, pose a significant barrier to affordability and widespread adoption. Additionally, market overcapacity leads to increased competition and potential bankruptcies among smaller firms. The heavy reliance on government subsidies, while initially successful in driving demand, raises concerns about market dependency and sustainability in the long run. Furthermore, consumer preferences in China tend to favour established international brands, which presents challenges for domestic manufacturers striving for brand recognition and consumer trust. This essay examines these critical issues and proposes practical solutions to maintain sustainable growth. Strategies such as investment in technological innovation, forming strategic partnerships, transitioning from direct subsidies to infrastructure investments, and establishing unified standards are discussed as potential approaches to overcoming these challenges. By adopting these solutions, China can maintain its leadership in the global EV market and achieve sustainable growth.